Pemetaan Bibliometrik Terhadap Penelitian dan Perkembangan Publikasi Dominating Graph - Dewi, Novian Riskiana (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to conduct bibliometric mapping of research and publication developments related to dominating graphs in the period from 2015 to 2024. The data was obtained through the google scholar database using Publish or Perish software with the keyword "Dominating Graph". The metadata collected was focused on journal articles in the 2015-2024 time frame, the maximum result was set at 1000, resulting in a total of 930 documents. The data is exported to collect all information related to article titles, authors, cities, references, and keywords, so that it can be easy to enter references with the help of VOSViewer software. The results of the study show a significant trend of increasing the number of publications in 2018 and decreasing in the following years. Visualization using Network, Overlay, and Density Visualization shows that the themes and relationships between relevant research topics have been successfully identified, providing new insights for the development of future graph dominating research